Sertifikasi Halal Dan Pengaruhnya Terhadap Kepuasan Turis Dan Loyalitas Destinasi - Haryeni, Haryeni (LPPM Universitas Dharma Andalas, 2025)
The purpose of this study was to determine the effect of halal certification on halal culinary on tourist satisfaction, the effect of tourist satisfaction on destination loyalty, and the effect of halal certification on destination loyalty mediated by tourist satisfaction. The population in this study were local tourists visiting halal tourist destinations in West Sumatra, namely Padang City. A series of exploration and confirmation analysis factors were used to assess the research construction, validity, and reliability of the composite. The number of samples in this study was 150 respondents. The data analysis technique used in testing the hypothesis of this study was the utilization of the Partial Least Square (PLS) program. Based on the results of the study, halal certification does not have a significant effect on tourist satisfaction. Tourist satisfaction has a significant effect on destination loyalty, and tourist satisfaction does not mediate the relationship between halal certification and destination loyalty.